Novel Rechargeable Lithium-Ion Battery Based on a Cathode of Potassium-Cobalt(Ii) Octacyanomolybdate - Herrera-Diaz, F; Herrera-Diaz, F (Institute of Physics, 2021)
In this work, the influence of the synthesis parameters (concentration, temperature, and reaction time) on the electrochemical performance of potassium-cobalt(II) octacyanomolybdate (KCoOCM) as a cathode material for its application in lithium-ion batteries was studied. The compound was synthesized hydrothermally using a chemometric approach and characterized by different techniques. The KCoOCM showed a change in its morphology from prismatic structures to nanorods according to the synthesis conditions. Additionally, there was an influence on the specific capacity as a function of the synthesis parameters, i.e., precursor s concentrations, temperature, and reaction time. The capacity values reached by the material was 50 mAh g-1, which is close to the theoretical value of the KCoOCM (60 mAh g-1). The statistical method employed would allow finding a condition where it is possible to maximize the capacity value of the material, which has been scarcely studied in this area. Finally, the performance of a lithium-ion battery based on a cathode of KCoOCM is reported for the first time in literature. © 2021 The Electrochemical Society ("ECS"). Published on behalf of ECS by IOP Publishing Limited.